Pengembangan Aplikasi Penjualan Furniture Berbasis Visual Studio untuk Optimalisasi Proses Transaksi - Ramadhani, Amaliya Izzah; Azzahra, Rika Ichsani; Basatha, Rizky (Al-DYAS, 2025)
The development of a furniture sales application using Visual Basic addresses inefficiencies in traditional sales systems, such as errors in manual transactions and challenges in managing inventory and customer data. The objective of this study is to create a practical, user-friendly application to improve operational processes and support small and medium-sized businesses. The application was developed using Visual Basic within Microsoft Visual Studio 2022, with MySQL as the database and phpMyAdmin for database management. The methodology included designing a system to manage product inventory, customer data, and sales transactions while integrating a reporting feature. Data collection involved analyzing existing sales systems, while data analysis focused on usability testing and performance evaluation. Key findings indicate that the application enhances efficiency by reducing transaction errors, simplifying inventory management, and enabling store owners to monitor sales trends effectively through automated reports. The application also improves user experience by offering a simple and intuitive interface for daily operations. In conclusion, the developed furniture sales application provides a robust solution for small and medium enterprises, supporting better business management, minimizing human errors, and increasing productivity.